PENGARUH EFIKASI DIRI TERHADAP PERSEPSI DALAM PEMBELAJARAN SECARA INDIVIDUAL DENGAN PERILAKU PEMBELAJARAN DI DALAM TIM SEBAGAI VARIABEL MODERASI PADA KARYAWAN PT.BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG BANDA ACEH - Rizki Alhadi, Ade Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This research aimed to measure the effect of sell-efficacy perception of individual learning with team-learning behavior as a moderating variable. This study also address the interaction of team-learning behavior on perception of individual learning. The sample used in this research are employess of PT. Bank Rakyat Indonesia (Persero) Tbk.Cabang Banda Aceh. The instrument of collecting data in this research is questionnaire. The sampling technique used in this study is Simple random sampling. With a total of 110 questionnaires were distributed and just only 97 could be collected. Method of data analysis are Moderate Regression Analysis (MRA) which used as methods of analysis to determine the effect of all the variable involved. The result of this study indicate that sell-efficacy have significant effect on perception of individual learning. team-learning behavior has significant effect on perception of individual learning. In addition abtained results that team-learning behavior has moderated on the effect of sell-efficacy to perception of individual learning on employees PT. Bank Rakyat Indonesia (Persero) Tbk.Cabang Banda Aceh.Keywords: sell-efficacy, team-learning behavior, perception of individual learning